(untitled) (Journal of Science Foundation, 2013)
The present research work was conducted from July 2008 to June 2009 to investigate intensity of infestation of parasites in freshwater fishes and the impact of fish diseases on fish production in northern region of Bangladesh. Possibility of out break of diseases due to deterioration of environmental factors of water bodies was included in this study. The diseases identified were ulcer diseases, EUS (Epizootic Ulcerative Syndrome), Ichthyophthiriasis, Trichodiniasis, Chilodoneliasis, Myxoboliasis, Dactylogyrosis, Gyrodactylosis, Argulosis, Pernicious anaemia, Red spot disease, Red Pest of freshwater eel, Mouth fungus, Branchiomysis, Abdominal dropsy and whirling disease. The infestation more occurred in young fishes than in adult fishes. The overall water qualities of water bodies fluctuated from July 2008 to June 2009. Physicochemical parameters have more or less significant combined effect on the deterioration of water quality as well as fish diseases. Gills were the most affected sites and parasites damaged gill filaments by rupturing blood capillaries, causing necrosis, coagulation and hemorrhage. The present study revealed the prevalence of different organisms in fishes, which are potential pathogen for them. Fishes were infested by parasites and other pathogens. From overall study it was observed that the parasites, bacteria and fungus were most important pathogen for outbreak of diseases. It was also observed that there was a direct relation between disease outbreak among fishes and environmental factors. Low alkalinity reduces the buffer capacity of water and badly affects the pond ecosystem, which in turn cause stress to the fish and become more susceptible to diseases. In case of low aquatic environmental temperature fish reduces metabolic activities, which in turn makes the fish more susceptible during the winter period towards parasitic infection. DOI: http://dx.doi.org/10.3329/jsf.v9i1-2.14655 J. Sci. Foundation, 9(1&2): 125-131, June-December 2011